2012
DOI: 10.1039/c1cc16045a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure on Cu-btc: framework compression vs. guest inclusion

Abstract: Here we present detailed structural data on the effect of high pressure on Cu-btc. Application of pressure causes solvent to be squeezed into the pores until a phase transition occurs, driven by the sudden compression and expansion of equatorial and axial Cu-O bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 18 publications
(19 reference statements)
6
60
1
Order By: Relevance
“…Though these guests are not part of the extended framework skeleton, it has been shown that they can affect the mechanical behavior (e.g., compressibility) of the respective MOF quite drastically. 30,32 We have recently demonstrated that this is particularly true for flexible and responsive MOFs, which are able to change their structure reversibly upon adsorption of different guests. 57 By analogy with the previously discussed [Zn 2 (bdc) 2 (dabco)] n framework, [Zn 2 (NO 2 -bdc) 2 (dabco)] n (NO 2 -DMOF; NO 2 -bdc = 2-nitro-1,4-benzenedicarboxylate) undergoes distinct changes in network geometry upon exchange of guest molecules (Fig.…”
mentioning
confidence: 99%
“…Though these guests are not part of the extended framework skeleton, it has been shown that they can affect the mechanical behavior (e.g., compressibility) of the respective MOF quite drastically. 30,32 We have recently demonstrated that this is particularly true for flexible and responsive MOFs, which are able to change their structure reversibly upon adsorption of different guests. 57 By analogy with the previously discussed [Zn 2 (bdc) 2 (dabco)] n framework, [Zn 2 (NO 2 -bdc) 2 (dabco)] n (NO 2 -DMOF; NO 2 -bdc = 2-nitro-1,4-benzenedicarboxylate) undergoes distinct changes in network geometry upon exchange of guest molecules (Fig.…”
mentioning
confidence: 99%
“…Sc2BDC3(ip) does not therefore experience the stabilizing effect of channel 'super-filling' which occurs with methanol, which also occurs in other MOFs with one, two and three-dimensional channel connectivity. 15,23,30 Larger di-branched hydrocarbons can also penetrate into the pores of Sc2BDC3 at high pressures. Using 2,3-dimethylbutane and 2-methylheptane as hydrostatic media, a similar transformation is observed (see Figure 5a and b), though in each case the rotation is not as significant as in Sc2BDC3(ip): 21.2° for 2,3-dimethylbutane and 28.2° for 2-methylheptane.…”
mentioning
confidence: 99%
“…Beamline I19 has played a pivotal role in the recent development and exploitation of highpressure crystallographic methods and it has already contributed to landmark high-pressure investigations of well-known MOFs [30][31][32][33][34][35]. We have begun studies of the behaviour of our own more flexible MOFs, several of which possess outstanding gas storage or separation properties, at pressures of up to 100 kbar.…”
Section: Continuing and Future Activitiesmentioning
confidence: 99%